FRI0125 Quantification of tumour necrosis factor in ankylosing spondylitis patients during adalimumab treatment. (12th June 2018) - Berkhout, L.; Ruwaard, J.; l'Ami, M.J.; Wolbink, G.; Rispens, T.
Abstract : Background: Tumour necrosis factor- (TNF) inhibitors, including adalimumab, are widely used in the treatment of inflammatory autoimmune diseases. Longitudinal (drug-bound) TNF levels in rheumatoid arthritis (RA) patients increased upon adalimumab treatment, and remained stable over two years follow-up. Low TNF levels at week four were associated with a significantly higher frequency of anti-drug antibodies (ADAs) at subsequent time points, significantly less methotrexate (MTX) use at baseline and a significantly reduced clinical response after 52 weeks (unpublished data). Objectives: To investigate TNF levels during adalimumab treatment in ankylosing spondylitis (AS) patients and to compare this with TNF levels measured in RA patients. Methods: Longitudinal TNF levels were quantified in 76 consecutive AS patients during adalimumab treatment, using a competition enzyme-linked immunosorbent assay (ELISA). This ELISA is drug-tolerant, which enables the quantification of TNF in the presence of large amounts of TNF-inhibitor. The relationship between TNF levels, drug levels and ADA detection was evaluated. Results: At baseline, TNF levels were close to the detection limit, but levels increased during adalimumab treatment (figure 1A ; stratified to concomitant MTX use; black lines represent median TNF (IQR)). The increase in TNF was more gradual in patients treated with adalimumab monotherapy, compared to the increase in TNF levels in patients concomitantly treated with MTX (only 9% of the patients). Similar results were found for adalimumab-treated RA patients, stratified to concomitant MTX use (figure 1B ; Black lines show median (IQR)). Furthermore, at week four, low TNF levels in AS patients tended to associate with a higher frequency of ADAs after 24 weeks. Conclusions: This is the first study describing an increase in TNF levels in AS patients during one year of adalimumab treatment. The dynamics in TNF levels is different for patients concomitantly treated with MTX, compared to patients treated with adalimumab monotherapy. Low TNF levels at week four tended to associate with a higher frequency of ADAs, which is potentially associated with the low frequency of MTX use at baseline. Disclosure of Interest: L. Berkhout: None declared, J. Ruwaard: None declared, M. l'Ami: None declared, G. Wolbink Grant/research support from: Pfizer, Speakers bureau: Pfizer, UCB, AbbVie, Biogen, BMS, T. Rispens Grant/research support from: Genmab, Speakers bureau: Pfizer, AbbVie, Regeneron